Groningen frailty indicator in older patients with end-stage renal disease. (21st October 2015) - Meulendijks, F. G.; Hamaker, M. E.; Boereboom, F. T. J.; Kalf, A.; Vögtlander, N. P. J.; van Munster, B. C.
Abstract: Background : Currently over 55% of end-stage renal disease (ESRD) patients are aged ≥60 years and patients >75 years represent the fastest growing segment of the dialysis population. We aimed to assess whether the Groningen frailty indicator (GFI) can be used to distinguish fit older ESRD patients, likely able to tolerate and benefit from dialysis, from frail older patients who need further evaluation with a geriatrician's comprehensive assessment. Methods : All patients aged ≥65 years visiting the pre-dialysis unit at the Gelre hospital between 2007 and 2013 were included and underwent the GFI ( n = 65). Patients with GFI ≥ 4 (frail) were referred for geriatric consultation ( n = 13). Results of the GFI and nephrologists' evaluation were compared with geriatrician's assessment. Survival rates and outcomes after one year of follow up were recorded. Results : Twenty patients (32%) were identified as frail. Of the problems identified by the geriatrician in 13 patients, 55% were not reported in the nephrologists' notes. The first year after inclusion, 30% of patients with a GFI ≥ 4 died, compared to 9% of fit patients ( p = 0.04). Moreover, 90% of frail patients had been hospitalized one or more times, compared to 53% in the fit group ( p = 0.005). Conclusion : Although the GFI can be a useful instrument to identify ESRD patients at risk, both the GFI and the nephrologists' assessment failed to identify specific geriatric impairments. Further research is needed to develop a specific frailty indicator for ESRD patients and to determine the value and effect of a comprehensive geriatric assessment in ESRD patients.